2020
DOI: 10.1002/jbio.201960232
|View full text |Cite
|
Sign up to set email alerts
|

Optimal imaging windows of indocyanine green‐assisted near‐infrared dental imaging with rat model and its comparison to X‐ray imaging

Abstract: In this study, we used rat animal model to compare the efficiency of indocyanine green (ICG)-assisted dental near-infrared fluorescence imaging with X-ray imaging, and we optimized the imaging window for both unerupted and erupted molars. The results show that the morphology of the dental structures was observed clearly from ICG-assisted dental images (especially through the endoscope). A better image contrast was easily acquired at the short imaging windows (<10 minutes) for unerupted and erupted molars. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Although application of PB is a feasible procedure, detection of fine (neo) vasculature system is often not possible due to its relatively low sensitivity by optical wave length-light. Hence, visualization and in vivo imaging by various dye injection is becoming frequently reported [ 21 24 ]. Injected PB after the current procedure showed the successful ligation and enlargement of the main L.V.…”
Section: Resultsmentioning
confidence: 99%
“…Although application of PB is a feasible procedure, detection of fine (neo) vasculature system is often not possible due to its relatively low sensitivity by optical wave length-light. Hence, visualization and in vivo imaging by various dye injection is becoming frequently reported [ 21 24 ]. Injected PB after the current procedure showed the successful ligation and enlargement of the main L.V.…”
Section: Resultsmentioning
confidence: 99%
“…15 Early detection plays an important role in the diagnosis of a crack, which could significantly limit further growth of the crack and save the tooth. 10,13 In our previous pilot studies, we demonstrated the feasibility of ICG-NIRF dental imaging based on both a rat model 40,41,44 and human extracted teeth. 42,43 These results showed the promise of using ICG-NIRF dental imaging for crack detection.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In our previous research we demonstrated the feasibility of indocyanine green (ICG) for dental imaging in the rat model and human extracted tooth. [39][40][41][42][43][44] We found that ICF-NIR fluorescent (ICG-NIRF) imaging could diagnose several typical diseases in human extracted teeth, such as caries lesions, decay, and insidious caries. 42,43 In particular, we compared ICG-NIRF dental imaging with X-ray imaging.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 19 27 Our previous studies have successfully demonstrated ICG-NIR fluorescence (ICG-NIRF) dental imaging in both human-extracted tooth and rat models. 17 , 28 32 …”
Section: Introductionmentioning
confidence: 99%
“… 17 , 47 In our previous rat model studies, ICG-NIRF dental imaging was only performed in the short NIR wavelength. 29 32 Few studies have reported using ICG for dental imaging in the second NIR windows to our best knowledge.…”
Section: Introductionmentioning
confidence: 99%